Pengaruh Model Pembelajaran Advance Organizer Menggunakan Video Pembelajaran Terhadap Hasil Belajar Fisika Peserta Didik Kelas XI - Nurul Hamdanillah; Ahmad Harjono; Susilawati Susilawati (Department of Physics Education, Universitas Mataram, 2017)
This research is aimed to identify the effect of advance organizer learning model through video learning towards physics learning outcome of second grade students MIA SMAN 2 Labuapi. Advance Organizer is a learning model which consists of 3 phases: presentation of Advance Organizer, presentation of learning assignment or learning of material, and strengthen the cognitive structure. There are three domains of learning objective concerned in the study, which are, first cognitive aspect from C1 until C6 (knowledge, comprehension, application, analysis, synthesis and evaluation), second is affective aspect and the last is psychomotor aspect. The student cognitive learning outcome was done by using objective test. Based on data analysis, t count > t table, as the result, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted that there was the influence of advance organizer learning model through video learning towards physics learning outcome ofÃÂ second grade students MIA SMAN 2 Labuapi.